An Exploration of the Optimal Solution for the Tuberculosis Transmission Model considers the Post-recovery Treatment using Optimal Control Theory - Sanubari Tansah Tresna; Choirul Basir; Usep Rahmat; Enggar Prasetyawan (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2026)
Tuberculosis, also known as TB, is among the most communicable diseases. It is strenuous to detect TB infection early, so the number of cases increases over time. Consequently, the cost of treating the TB-infectious sufferer is getting higher. However, since the recovered people from TB can become infected again, the post-treatment intervention needs to be conducted. Many mathematical models have been developed to study TB transmission among people. However, the study of cost-effectiveness analysis is not well-studied. Therefore, we are proposing a reformulated model of TB transmission into an optimal control model by considering the post-treatment intervention to reduce the cases of re-infected TB. The numerical simulations are performed to figure out the projection of its population dynamics under TB transmission. Next, we calculate the Average Cost-Effectiveness Ratio (ACER) and Incremental Cost-Effectiveness Ratio (ICER) to explore the most cost-effective strategy.